The story of art. - Gombrich, E. H. 4 0 16; 5 (Oxford : Phaidon, 1979)
Text and 398 illustrations survey the history of art from prehistory to the present.
Young Adult;Young Adult
Keywords: 2 -- 0; 6; History. -- Art -- 20; 20; 2